The Concept of the Admissibility of Evidence in Lithuanian Civil Procedure and Arbitration - Bartkus, Jurgis (Teisė, 2022)
This article analyzes the concept of admissibility of evidence in Lithuanian civil proceedings and arbitration. The first part of the article reviews the past and current legislation, case law and doctrine, which reveal the concepts of the admissibility of evidence in both civil and arbitral proceedings.The second part of the article provides a critical assessment of these concepts. It is proposed to improve the concept of the admissibility of evidence in civil proceedings, and an alternative of this concept is presented. As far as arbitration law is concerned, it is acknowledged that the concept of the admissibility of evidence in arbitration causes legal uncertainty in the proceedings, which forces to consider possible corrections to this concept.
Keywords: civil procedure; arbitration; admissibility of evidence; evidence